Multidrug resistant bacteria associated with a fresh fruit and vegetables sold in Lokoja market, Kogi State, Nigeria - Gbolabo Odewale; Motunrayo Jibola-Shittu; Nosakhare Omosule; Titilope Esan (Microbes and Infectious Diseases, 2025)
Background: Fruits and vegetables are an extraordinary dietary source of nutrients, phytochemicals, vitamins, and fiber and are globally recommended as part of a healthy diet. Despite the nutritional benefits, their surfaces could become contaminated with pathogenic bacteria causing illness or death. This study aimed at identifying bacteria species associated with surfaces of fruits and vegetables sold in old and international markets in Lokoja. Methodology: Thirty fruits and vegetables were purchased from two major markets and processed according to standard techniques. Total aerobic plate count (TAPC) was estimated by culturing on selected media and isolates obtained were biochemically characterized. Resistance patterns of isolates were determined by the disk diffusion method using commercially available antibiotics. Results: The mean bacteria count from the old market ranged from 4.56 X 106 – 7.0 X 106, while that of international market ranged from 4.45 X 106 – 4.98 X 106. The prevalence of bacteria isolated from the fruits and vegetables were Klebsiella pneumoniae (28.2%), Salmonella species (sp.) (20.5%), Escherichia coli (15.4%), Staphylococcus aureus (10.2%), Enterobacter sp. (7.7%), Pseudomonas aeruginosa (5.1%), and Bacillus sp. (5.1%) and Proteus vulgaris (2.7%). All isolates were entirely resistant (100%) to ampicillin and oxacillin, gentamycin (94.9%), ciprofloxacin (69.2%), cefotaxime (51.3%), tetracycline (43.6%), while isolates were least frequently resistant to ceftazidime (41.0%). Conclusion: The presence of multidrug resistant isolates indicates that fresh fruits and vegetables sold in Lokoja are potential vehicles for transmitting food borne illnesses. Food safety measures should be taken by retailers and consumers to mitigate the spread of food borne illnesses.